Retrieval activates related words more than presentation. Issue 9 (21st October 2018) - Hausman, Hannah; Rhodes, Matthew G.
ABSTRACT: Retrieving information enhances learning more than restudying. One explanation of this effect is based on the role of mediators (e.g., sand-castle can be mediated by beach ). Retrieval is hypothesised to activate mediators more than restudying, but existing tests of this hypothesis have had mixed results [Carpenter, S. K. (2011). Semantic information activated during retrieval contributes to later retention: Support for the mediator effectiveness hypothesis of the testing effect. Journal of Experimental Psychology: Learning, Memory, and Cognition, 37 (6), 1547–1552. doi:10.1037/a0024140 ; Lehman, M., & Karpicke, J. D. (2016). Elaborative retrieval: Do semantic mediators improve memory? Journal of Experimental Psychology: Learning, Memory, and Cognition, 42 (10), 1573–1591. doi:10.1037/xlm0000267 ]. The present experiments explored an explanation of the conflicting results, testing whether mediator activation during a retrieval attempt depends on the accessibility of the target information. A target was considered less versus more accessible when fewer versus more cues were given during retrieval practice (Experiments 1 and 2), when the target had been studied once versus three times initially (Experiment 3), or when the target could not be recalled versus could be recalled during retrieval practice (Experiments 1–3). A mini meta-analysis of all three experiments revealed a small effect such that retrieval activated mediators more than presentation, but mediator activation was not reliably related to target accessibility. Thus, retrieval may enhance learning by activating mediators, in part, but these results suggest the role of other processes, too.